VD_FINDINFO Arrêt / 2012 / 340 vom 9. Februar 2012 - VD Tribunal cantonal (2012)
RENVOI DANS UN HÔPITAL OU UN HOSPICE, INTERDICTION, MALADIE MENTALE | 369 al. 1 CC, 392 ch. 1 CC, 393 ch. 2 CC, 379 CPC, 393 CPC, 174 al. 2 CDPJ